(untitled) (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2026)
Employee productivity is a critical determinant of organizational performance, particularly in the highly competitive banking industry. Compensation practices are widely recognized as significant factors influencing employee behavior and work performance; however, the effectiveness of compensation components may differ according to employees’ motivational levels. Grounded in Herzberg’s Two-Factor Theory, this study examines the effect of compensation components namely basic salary, bonus, allowances, incentives, and benefits on employee productivity in Nepalese commercial banks, while also analyzing the moderating role of employee motivation. The study employed a quantitative research design using descriptive and causal research approaches. Primary data were collected through structured questionnaires administered to 394 employees from selected commercial banks in Nepal using a five-point Likert scale. The collected data were analyzed through descriptive statistics, Pearson correlation, multiple regression, and moderation analysis using SPSS software. The findings reveal that incentives have a significant positive effect on employee productivity (β = 0.265, p < 0.001), whereas basic salary, bonus, allowances, and benefits demonstrate relatively weak or statistically insignificant direct effects. Moreover, employee motivation significantly moderates the relationship between compensation components particularly basic salary, bonus, and incentives and employee productivity by strengthening their positive influence. The regression model explains approximately 10 percent of the variation in employee productivity, indicating that compensation alone is insufficient to achieve higher performance outcomes. The study concludes that performance-based incentive systems integrated with effective motivational practices are essential for enhancing employee productivity in Nepalese commercial banks. The findings further support Herzberg’s distinction between hygiene factors and motivators and provide practical implications for developing compensation strategies that improve employee motivation and organizational performance.